Christian religious models of Taras Shevchenko in the discursive field of Ivan Ogiienko (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article analyzes the religiousness of Taras Shevchenko through the lens of research of Ivan Ohienko (metropolitan Ilarion). The main emphasis is on factors that formed the Christian worldview of the writer; the value of Christian objects of worship are investigated from the point of view of religion, folklore and the poet; educational, moral and educational functions are analyzed in Shevchenko's works.
Keywords: religiousness; Christian worldview; canon of the church; style; text; context